(untitled) (Baghdad Science Journal, 2021)
Most studies indicated that the values ​​of atmospheric variables have changed from their general rates due to pollution or global warming etc. Hence, the research indicates the changes of direct solar radiation values ​​over a whole century i.e. from 1900 to 2000 depending on registered data for four cities, namely (Mosul - Baghdad - Rutba - Basra. Moreover, attemptsto correlate the direct solar radiation with the temperature values have been ​​recorded over that period. The results showed that there is a decreasing pattern of radiation quantities over time throughout the study period, where the value of direct radiation over the city of Baghdad 5550 w/m2 was recorded in the year 1900, but this ratio decreased clearly to approximately 5400 w/m2 in the year 2000, which is perhaps due to the increase of general pollution rates in the atmosphere. The results also showed that the city of Rutba recorded the highest annual rate of radiation quantities, and Baghdad with Mosul recorded the lowest radiation ratios compared to the rest of the cities, in addition to that there was a large convergence of radiation ratios between them to some extent. The results showed that there is a sharp drop in radiation ratios, specifically in the years1980and 1990. As for the extent of the relationship for solar radiation with temperature levels throughout the study period, it was found that there is an inverse relationship between them, and this confirms that the cause of high temperatures is not because of increased solar radiation, but it may rather due to other reasons such as increased greenhouse gases.